Benign colonic metaplasia at a previous stoma site in a patient without adenomatous polyposis. (2nd November 2015) - Prouty, Megan; Patrawala, Samit; Vogt, Adam; Kelleher, Michael; Lee, Michael; Parker, Douglas C.
Abstract : There are few reported cases of cutaneous intestinal metaplasia or primary adenocarcinoma arising at the ileostomy site following panproctocolectomy. These complications have been seen almost exclusively in patients with familial adenomatous polyposis and inflammatory bowel disease (IBD). However, benign intraepidermal colonic mucosa at a reversed ileostomy site in a patient without familial adenomatous polyposis or IBD has not been documented. We report a case of a 51‐year‐old female with a history of colonic adenocarcinoma who presented with pruritic, erythematous, scaly plaques on the right lower abdomen, present since reversal of her ileostomy in 2007. Skin biopsy revealed benign foci of colonic epithelium with no evidence of adenomatous change. Benign intraepidermal colonic mucosa was diagnosed based on histopathologic findings and immunohistochemistry. To our knowledge, this is the first case of intraepidermal benign colonic metaplasia forming in a patient following ostomy reversal. The case emphasizes the importance of patient education and physical examination of the stoma or stoma remnants for detection of unusual or changing lesions due to the risk for malignant transformation. It also demonstrates that benign colonic mucosa should be considered in the differential diagnosis when evaluating lesions near ileostomy sites, regardless of whether the patient has a history of familial adenomatous polyposis or IBD.